National legislative systems and foreign standards and regulations: The case of International Financial Reporting Standards adoption - Dima, Bogdan; Dima (Cristea), Stefana Maria; Moldovan, Nicoleta; Pirtea, Marilen Gabriel (MPRA Paper, 2010)
This study is focused on the linkages between the legislative families as descriptors of national legislative systems and International Financial Reporting Standards (IFRSs) issued by the International Accounting Standards Board (IASB). We consider such analysis as a case study for the more general issue of explaining the preferences of national regulators in the adoption of foreign norms, rules, standards and practices. By using a dataset of 162 jurisdictions and dummy variables designed to capture the current stage of IFRSs adoption and, respectively, the taxonomy of their legislative systems, we find that a full IFRSs adoption is more likely to occur in countries which have principles-based on legislative mono-systems. In addition, we observe that a strong rule of law, with an effective mechanism of property rights reinforcement, as well as the pre-adoption existence of a pro-growth set of public policies can contribute to the encouragement of IFRSs adoption.
Keywords: IFRSs adoption; Legislative families

L'acte uniforme relatif au droit commercial général - Loir, Romain (Revue juridique de l'Océan Indien, 2010)

OHADA et droit des sûretés - Bernard-Ménoret, Ronan (Revue juridique de l'Océan Indien, 2010)
Keywords: Comparaison dispositif OHADA Code civil français; Droit comparé; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires Droit des sûretés français

Le droit des affaires "sans" l'OHADA : l'emprise du Civil Law / Common Law dans un système de droit mixte (le regard de Maurice) - Gunputh, Rajendra-Parsad (Revue juridique de l'Océan Indien, 2010)
Keywords: Actes de commerce; Activité de la société; Code civil mauricien; Code de commerce français; Code de commerce mauricien; Common law; Droit des affaires; Droit des sociétés commerciales; Fonds de commerce; OHADA; Objet social; Organisation pour l'harmonisation en Afrique du droit des affaires droit mauricien; Régimes matrimoniaux; action en responsabilité; affectio societatis; apports; article 1382 du Code civil; capacité civile; civil law; commerçant; dispositions impératives du Compagnies Act 2001; droit mixte; femme mariée; nom commercial

L'harmonisation du droit des affaires en Afrique par l'OHADA : Synthèse des travaux - Issa-Sayegh, Joseph (Revue juridique de l'Océan Indien, 2010)
Keywords: Extension des Actes Uniformes; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires Sécurité juridique; Uniformisation du droit des affaires; extension territoriale de l'OHADA; sécurité judiciaire

Le droit de l'OHADA : une source d'inspiration pour les législateurs nationaux ? - Ponsot, Dominique (Revue juridique de l'Océan Indien, 2010)
Keywords: Apport doctrinal; Apport universitaire; Droit OHADA; Droit commercial régional; Intégration; Membre de l'organisation; Organisation pour l'harmonisation en Afrique du droit des affaires actes uniformes; Pays non-membres; Pays tiers; Reprise du droit OHADA; Sources du droit

The New African Law: Beyond the Difference Between Common Law and Civil Law - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

Trends on the Harmonization of Contract Law in Africa - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

Legal Challenges and Strategies for Comparison Shopping and Data Reuse - Zhu, Hongwei; Madnick, Stuart E. (Journal of Electronic Commerce Research, 2010)
New technologies have been continuously emerging to enable effective reuse of an ever-growing amount of data on the Web. Innovative firms can leverage the available technologies and data to provide useful services. Comparison-shopping services are an example of reusing existing data to make bargain-finding easier. Certain reuses have caused conflicts with the firms whose data has been reused. Countries in the European Union have implemented the Database Directive to provide legal protection for database creators, but the impact and the interpretation of the new law are unclear and still evolving. Lawmakers in the U.S. have not decided on a policy concerning database protection and data reuse. Both data creating and data reusing firms need to develop strategies to operate effectively in this uncertain environment. Comparison-shopping and other data reuse services face similar legal and strategic challenges. Thus we address these challenges in the broader data reuse context. We use economic reasoning to formulate strategies in anticipation of the likely policy choices and interpretations of existing legislation. Both data creating firms and data reusing firms should focus on innovative ways of using or reusing data to create differentiated products and services. For firms that gather data from multiple sources, they can also use the insights gained from integrated data to provide other value-added services.

On the Development of West African Accounting System - Moussa, Boka (International Journal of Business and Management, 2010)
The authorities of the West African Economic and Monetary Union UEMOA fully understand that accounting plays the significant role in the process of economic development and regional integration in the member states. They decided to establish a common new accounting system, called West African Accounting System (SYSCOA). The accounting system has been developed on the initiative of the Central Bank of West African States

International Investment Law and Media Disputes: A Complement to WTO Law - Peterson, Luke Eric (Transnational Corporations Review, 2010)
The recent high-stakes dispute between Google and China over censorship and cyber-security has spawned renewed discussion of the international trade law protections that internet and media companies may enjoy. Less recognized, however, is a perhaps more powerful legal tool in the arsenal of internet and media companies engaging in cross-border investments, namely international investment law.
Keywords: China; international investment; law; media

The Role of South Africa in SADC Regional Integration: the Making or Braking of the Organization - Amos, Saurombe (Journal of International Commercial Law and Technology, 2010)
Read on Neliti

La nullité partielle d’une clause de non-concurrence : de l’affaire Cameron à l’affaire Shafron - Bouchard, Charlaine (Revue du notariat, 2010)

De la démocratie locale dans certaines banques coopératives - Caire, Gilles (Revue internationale de l'économie sociale, 2010)
Cet article s’intéresse aux pratiques démocratiques des banques coopératives en prenant appui sur la description du déroulement de deux assemblées générales de caisses locales. Sans prétendre aucunement à la représentativité, l’étude de terrain permet cependant de mettre en exergue certaines difficultés à faire vivre dans les structures de très grande taille les grands principes coopératifs : la libre adhésion, l’égalité de vote, la libre participation à la gestion et l’absence de but lucratif des représentants élus. Elle permet aussi de souligner l’absence de débat sur la construction d’un projet alternatif au fonctionnement financier capitaliste. This article looks at the democratic practices of cooperative banks based on how two local branches conducted their AGMs. While not claiming to be representative, the field research does however identify certain difficulties that very large-scale organizations face in putting into practice the main cooperative principles of open membership, one person – one vote, participation in decision-making, and the volunteer status of elected officials. The study also highlights the lack of debate about constructing an alternative to the way capitalist banks operate.

Droit et langues au Sénégal : les mythes fondateurs de l’unilinguisme d’Etat à l’épreuve des faits et des exigences de l’Etat de droit - Camara, Fatou Kiné (Droit sénégalais, 2010)

L’ordre juridique arbitral : réalité, utilité et spécificité - Gaillard, Emmanuel (McGill Law Journal, 2010)
L’ordre juridique arbitral existe-t-il ? S’il est perçu par les arbitres, souvent de manière intuitive mais très réelle, c’est qu’il existe. L’ordre juridique arbitral ne doit pas cependant être exclusivement conçu comme une représentation mentale du rôle des arbitres et de la source de leur pouvoir de juger. Il existe en tant que système de droit.

Vers une autonomie du droit coopératif ? - Hiez, David (Revue internationale de l'économie sociale, 2010)
L’histoire du droit coopératif français est marquée par la recherche d’une identité propre, tiraillée entre l’activité économique qui attire ces entreprises du côté des sociétés et les modalités de cette activité qui la rattachent au contraire aux associations. A l’heure où les spécificités coopératives sont questionnées, notamment par le droit communautaire, il est crucial d’approfondir cette identité. Seule la réaffirmation de la fracture entre coopérative et société est à même d’éviter le piège de la banalisation économique et, conséquemment, de la disparition juridique. The history of French cooperative law is marked by the search for a separate identity, torn between the business activity, which pulls these firms toward corporate law, and the way the business is run, which pulls them towards the laws governing nonprofits. At a time when the unique features of cooperatives are being challenged, in particular by EU legislation, this identity crucially needs to be defended. Only by reasserting the division between cooperatives and conventional firms can the trap of economic mainstreaming and consequently the disappearance of the legal form be avoided.

Rhapsodie sur la forme et le fond de l’harmonisation juridique - Leckey, Robert (Les Cahiers de droit, 2010)
L’auteur soutient dans le texte qui suit que les aspects par lesquels l’harmonisation du droit fédéral avec les droits communs provinciaux, qui a été entreprise par le gouvernement fédéral, diffère de son éponyme, l’harmonie musicale, soulèvent de cruciales controverses relatives aux théories du fédéralisme canadien et à la philosophie du droit. Tandis que le projet d’harmonisation juridique, tel qu’il a été conçu par ses architectes, peut être caractérisé comme une approche par le haut (top-down), approche conforme avec le positivisme juridique, l’harmonie musicale est mieux décrite comme une approche par le bas (bottom-up), approche plus conforme au pluralisme juridique. Si elle atteignait ses objectifs, l’initiative d’harmonisation juridique fédérale aurait comme effet d’enchâsser une vision selon laquelle le droit civil appartient exclusivement au gouvernement québécois. Or, malgré les ambitions de ses architectes, l’initiative d’harmonisation, dans sa mise en oeuvre, se révèle indisciplinée, soulevant de nombreux débats et interrogations. D’ailleurs, loin d’être un signe négatif, les débats et les désaccords font eux-mêmes partie de la pratique de l’harmonisation.

Enforcement of Arbitral Awards in Sub-Sahara Africa - Onyema, Emilia (Arbitration International, 2010)
As the world celebrated the fiftieth anniversary of the New York Convention in 2008 it became necessary to examine the enforcement regimes for arbitration awards in Sub-Sahara Africa. This article examines the provisions for the recognition and enforcement, and requirements for the setting aside of both domestic and international arbitral awards under the arbitration laws of OHADA member states, Nigeria and Sudan, as representative of the legal regimes in Sub-Sahara African countries. The New York Convention applies to Convention awards in half of the countries of Sub-Sahara Africa. It is therefore relevant to examine the requirements for the enforcement of non-Convention awards in those states that are members of the New York Convention, and also in those states that are not members of the New York Convention. Different arbitration laws and regimes apply in the three representative jurisdictions chosen for this comparative analysis and these are also representative of the legal regimes in those countries with arbitration laws in the region. Though a generally supportive tendency towards the enforcement of arbitral awards can be gleaned from the examination of some arbitration-related judgments, this article again highlights the importance for the remaining countries in the region yet to sign up to and implement the New York Convention to consider adopting it, and for more arbitration hearings to be held within the region.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Enforcement of Arbitral Awards; Sub-Sahara